Punishment as Suffering - Gray, David (2010)
When it comes to punishment, should we be subjectivists or objectivists? That is, should we define, measure, and justify punishment based on the subjective experiences of those who are punished or should we instead remain objective, focusing our attention on acts, culpability, and desert? In a recent series of high- profile articles, a group of contemporary scholars has taken up the mantle of subjectivism. In their view, criminal punishment is a grand machine for the production of negative subjective experiences-suffering. The machine requires calibration, of course. According to these scholars, the main standard we use for ours is comparative proportionality. We generally punish more serious crimes more severely and aim to inflict the same punishment on similarly situated offenders who commit similar crimes. In the views of these authors, this focus on comparative proportionality makes ours a rather crude machine. In particular, it ignores the fact that (1) different offenders suffer differently or to a different degree when subjected to the same punishment; (2) different offenders have different happiness baselines, which leads to disparities in the degree of suffering among offenders sentenced to the same punishment as measured by comparing their prepunishment baselines to their hedonic states during punishment; and (3) offenders' self-reported states of happiness and suffering vary over the course of a sentence, revealing inaccuracies in our objective assessments of severity. These scholars contend that a more sophisticated and rational approach would be to calibrate punishment according to the amount of suffering produced, trading objective measures of punishment-years in prison, etc.-for subjective measures. Looking forward to a day when advances in neuroscience and psychology will provide us with reliable qualitative and quantitative metrics of suffering, these scholars are setting the stage now, arguing that no matter our theory of criminal law and punishment-be we retributivists or utilitarians-we are obliged to dial the machine according to who is in its thrall and to titer both the form and extent of punishment so as to achieve just the right kind and amount of suffering